Hydrogels and Nanogels: Pioneering the Future of Advanced Drug Delivery Systems - Ernesto J. Delgado-Pujol; Guillermo Martínez; David Casado-Jurado; Juan Vázquez; Jesús León-Barberena; David Rodríguez-Lucena; Yadir Torres; Ana Alcudia; Belén Begines (Pharmaceutics)
Conventional drug delivery approaches, including tablets and capsules, often suffer from reduced therapeutic effectiveness, largely attributed to inadequate bioavailability and difficulties in ensuring patient adherence. These challenges have driven the development of advanced drug delivery systems (DDS), with hydrogels and especially nanogels emerging as promising materials to overcome these limitations. Hydrogels, with their biocompatibility, high water content, and stimuli-responsive properties, provide controlled and targeted drug release. This review explores the evolution, properties, and classifications of hydrogels versus nanogels and their applications in drug delivery, detailing synthesis methods, including chemical crosslinking, physical self-assembly, and advanced techniques such as microfluidics and 3D printing. It also examines drug-loading mechanisms (e.g., physical encapsulation and electrostatic interactions) and release strategies (e.g., diffusion, stimuli-responsive, and enzyme-triggered). These gels demonstrate significant advantages in addressing the limitations of traditional DDS, offering improved drug stability, sustained release, and high specificity. Their adaptability extends to various routes of administration, including topical, oral, and injectable forms, while emerging nanogels further enhance therapeutic targeting through nanoscale precision and stimuli responsiveness. Although hydrogels and nanogels have transformative potential in personalized medicine, challenges remain in scalable manufacturing, regulatory approval, and targeted delivery. Future strategies include integrating biosensors for real-time monitoring, developing dual-stimuli-responsive systems, and optimizing surface functionalization for specificity. These advancements aim to establish hydrogels and nanogels as cornerstones of next-generation therapeutic solutions, revolutionizing drug delivery, and paving the way for innovative, patient-centered treatments.